2005
DOI: 10.1080/00365590500329304
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose atorvastatin in severe chronic kidney disease patients: A randomized, controlled endpoint study

Abstract: Although atorvastatin reduced total and LDL cholesterol effectively it was not beneficial regarding the long-term outcomes of cardiovascular endpoints or survival. In contrast to other patient groups, patients with severe chronic kidney disease, especially those on dialysis, seem to derive limited benefit from this lower dose of atorvastatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 32 publications
1
38
0
1
Order By: Relevance
“…The included studies also showed low heterogeneity (I 2 =18.8%). In sensitivity analysis the exclusion of data from the trial lacking double blinding 17 did not significantly alter the results for infection related mortality (0.98, 0.84 to 1.14).…”
Section: Statin Treatment and Outcome Eventsmentioning
confidence: 93%
See 1 more Smart Citation
“…The included studies also showed low heterogeneity (I 2 =18.8%). In sensitivity analysis the exclusion of data from the trial lacking double blinding 17 did not significantly alter the results for infection related mortality (0.98, 0.84 to 1.14).…”
Section: Statin Treatment and Outcome Eventsmentioning
confidence: 93%
“…Three of the trials stated they were randomised but did not give the specific method of sequence generation, although they did state that investigators and participants were blinded to the process of randomisation. Except for one trial, 17 study quality was satisfactory overall and the trials were judged to be at low risk of bias (adequate sequence generation or allocation concealment, double blinding, and clear reporting of withdrawal rates and loss to follow-up). All trials were based on intention to treat analysis of long term treatments.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…They received more statins and had higher LDL cholesterol levels than the exposed subjects. The lipid-lowering effect of sevelamer hydrochloride on LDL cholesterol is well established [13,14], though this benefit has not been clearly associated with improved survival in HD patients [15,16]. In the present cross-sectional study, subjects exposed to the drug had significantly lower carotid IMT associated with lower LDL cholesterol, yet were prescribed fewer statins and aspirin.…”
Section: Discussionmentioning
confidence: 51%
“…No effect was found on all-cause mortality. A very small study (n=143) on adult patients with severe CKD (eGFR<30 ml/min/1.73m 2 ) and did not show statistically significant benefit from treatment with atorvastatin, but this could well be due to lack of power [30].…”
Section: Treatment Studies In Ckd Stages 2-4mentioning
confidence: 99%